Copper-mediated radiosynthesis of 18F- and 123I-radiolabelled PARP inhibitors - Chen, Z (2022)
This thesis aims to develop copper-mediated radiosynthesis to incorporate fluorine-18 and iodine-123 into FDA-approved poly(ADP-ribose) polymerase (PARP) inhibitors for cancer diagnosis and treatment, consisting the development of 18F-radiolabelled rucaparib for positron emission tomography (PET) application in cancer diagnosis and development of 123I-radiolabelled rucaparib and olaparib analogues as potential theragnostic agents for Auger therapy.